THE TIGRIS RIVER CREEP PHENOMENON RELATIONSHIPWITH BANK STONE CLADDING WITHIN BAGHDAD CITY - Rasheed, Moaied (Iraqi Journal of Science, 2024)
Tigris River meanders in Baghdad in several areas. Al-Jadiriyah, Al-Kadimia andAl-Atafia are the most important meander that meanders sharp and distinctive withsinuosity reach 4.1, 2 and 1.5 respectively Maps, aerial photographs and satelliteimages have been used, also surveyed field study, and by matching these maps,reflect and show the increased distortions intensity and slowly in the first half of thelast century because of the impact of repeated high discharges and for the erosion inthe concave side and the process of deposition in the convex side. After the middleof last century high discharges decreased due to the construction of dams and hencethe lower the activity of the river and stopped the river migration and confinedwithin the boundaries of the river downstream. The deposits of the study arearepresented by Holocene deposits of sand, silt and clay. The nature of the energy ofdeposition is determined by the river where the sand deposited first at the bottom ofthe river bed, which represents the beginning of the sediment cycle, the more fine